The Effect of Distributed Leadership and Perceived Organizational Support on Work Engagement: The Mediating Role of Psychological Capital in a Private SPK School in Tangerang Selatan - Yulian Candra; Stephanie Riady (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
Research on teacher work engagement identifies leadership and organizational support as job resources, but prior findings remain unclear about whether these resources act directly or by strengthening personal resources. This study integrates the Job Demands-Resources model and Conservation of Resources theory to examine psychological capital as a mechanism linking distributed leadership and perceived organizational support to teacher work engagement. A cross-sectional survey involved 129 teachers from kindergarten to senior high school in a private SPK school in Tangerang Selatan, Indonesia. Data were collected through a five-point Likert questionnaire and analyzed using PLS-SEM in SmartPLS 4. The measurement model showed acceptable reliability, convergent validity, and discriminant validity. Psychological capital was the strongest predictor of work engagement. Distributed leadership affected work engagement only through full mediation by psychological capital, whereas perceived organizational support had both direct and indirect effects. Schools should combine fair organizational support, coordinated distributed leadership, and psychological capital development.